Compressive Strength of Steel-Fiber Concrete with Artificial Lightweight Aggregate (ALWA) - Meity Wulandari; Tavio Tavio; I G. P. Raka; Puryanto Puryanto (Civil Engineering Journal, 2018)
In the last decade, there have been many innovations developed to replace the aggregate as material for concrete, particularly the coarse aggregate using the artificial lightweight aggregates a.k.a. ALWA. In the study, the main ingredient used to develop the artificial lightweight aggregates is the styrofoam. Styrofoam has a lightweight characteristic so that it can reduce the density of the concrete. If the density of the concrete can be lighter than the normal-weight concrete then the overall weight of the structure of a building will also be lighter. Thus, the shear force due to the earthquake will also be smaller so that the safety of the building becomes better. The styrofoam used was dissolved with the acetone solution and formed into granules in which the size resembled the coarse aggregate size of about 10 to 20 mm. The styrofoam which has been formed then dried up so that the texture becomes hard. In addition, steel fiber was also used as an added ingredient in concrete mixtures so that the concrete was highly resistant against cracking and was expected to increase the compressive strength of the concrete. ALWA compositions used to replace coarse aggregates were 0%, 15%, 50%, and 100%. While the composition of steel fiber used was 0%, 0.75%, and 1.5% of the total volume of the cylinder. The type of steel fiber used was hooked-end steel fiber with the diameter and the length of 0.8 mm and 60 mm, respectively. The results showed that the concrete with 15% styrofoam ALWA and 1.5% of steel fiber were able to produce optimum compressive strength by 28.5 MPa and the modulus of elasticity by 23,495 MPa. In addition, the use of Styrofoam ALWA as a substitution to the coarse aggregate can reduce the density of concrete as much as 5 to 35%.